2023
DOI: 10.3389/fphys.2022.1089669
|View full text |Cite
|
Sign up to set email alerts
|

Sugar perception in honeybees

Abstract: Honeybees (Apis mellifera) need their fine sense of taste to evaluate nectar and pollen sources. Gustatory receptors (Grs) translate taste signals into electrical responses. In vivo experiments have demonstrated collective responses of the whole Gr-set. We here disentangle the contributions of all three honeybee sugar receptors (AmGr1-3), combining CRISPR/Cas9 mediated genetic knock-out, electrophysiology and behaviour. We show an expanded sugar spectrum of the AmGr1 receptor. Mutants lacking AmGr1 have a redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…We found that the stimulant responses of workers were reduced significantly towards sucrose and fructose after the knockdown of SinvGR1 or SinvGR32b gene expression. In another social insect, the knockout of a fructose receptor (AmGR3) in honeybees significantly reduced the response to fructose, compared with wild-type bees (Degirmenci et al, 2023). The previous findings are also consistent with our results that knockdown of BtabGR11 and BtabGR1 expression in B. tabaci significantly interferes with sucrose sensing (Li et al, 2022;Aidlin Harari et al, 2023).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…We found that the stimulant responses of workers were reduced significantly towards sucrose and fructose after the knockdown of SinvGR1 or SinvGR32b gene expression. In another social insect, the knockout of a fructose receptor (AmGR3) in honeybees significantly reduced the response to fructose, compared with wild-type bees (Degirmenci et al, 2023). The previous findings are also consistent with our results that knockdown of BtabGR11 and BtabGR1 expression in B. tabaci significantly interferes with sucrose sensing (Li et al, 2022;Aidlin Harari et al, 2023).…”
supporting
confidence: 90%
“…In the Hymenoptera, TchiGR43a in the parasitoid Trichogramma chilonis could sense fructose for food sources (Liu et al, 2019). In the social insect honeybee, 2 receptors, AmGR1 and AmGR3, are sufficient for the basic perception of sugars (Degirmenci et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study indicated that thiacloprid exposure in the larval stage of honeybees interfered with antennal olfactory selectivity in adult honeybees. It is crucial for honeybees to detect floral scent compounds, which helps them to find host plants ( Değirmenci et al, 2022 ). A decreased selectivity toward floral volatiles might lead to problems in locating host plants and might affect the foraging efficiency ( Tison et al, 2016 ) or colony development of bees ( Ellis et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The colonies were identified to be free of bacterial diseases (American and European foulbrood), fungal diseases (Nosema, chalkbrood, and stonebrood), and viruses (deformed wing virus and acute honeybee paralysis virus) via PCR testing. The larvae were reared according to a standard protocol described by Schmehl et al ( Schmehl et al, 2016 ), which has been widely employed in numerous studies ( Chen et al, 2021 ; Değirmenci et al, 2022 ; Netschitailo et al, 2023 ). We confirmed the dependability of this larva-rearing approach, as we did not observe queen or queen-like honeybee emergence despite administering royal jelly to larvae aged >3 days.…”
Section: Methodsmentioning
confidence: 99%